Teachers' psychological resistance to digital innovation in jordanian entrepreneurship and business schools: Moderation of teachers' psychology and attitude toward educational technologies - AL-Takhayneh, Suhaib Khalid; Karaki, Wejdan; Hasan, Rashad Ahmad; Chang, Bang-Lee; Shaikh, Junaid M.; Kanwal, Wajiha (Frontiers in Psychology, 2022)
The current study aimed to highlight the factors that may influence teachers' psychological resistance to digital technologies in entrepreneurship and business schools. Theoretically grounded in Diffusion of Innovations Theory and the Theory of Planned Behavior, the current research investigates teacher psychological resistance to digital innovation, school culture and climate, and moderation of teacher attitudes toward educational technologies. A cross-sectional field survey of 600 business and entrepreneurship school teachers was conducted in Jordan. In this study, Partial Least Square Structural Equation Modeling (PLS-SEM) was used to assess the variables' "direct and moderating impacts" using the Smart PLS software 3.0. According to the results, school culture and school innovation climate had a considerable positive impact on teachers' resistance to digital innovation. Additionally, teachers' attitudes toward educational technologies moderated the relationship between study constructs in the framework. The study is a significant advance to the literature related to entrepreneurship, business education and digital innovation. Several key policy insights and recommendations for further research, as well as theoretical and practical implications are suggested.